2018
DOI: 10.1111/1440-1681.12913
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cell imbalance is associated with recurrent endometrial polyps

Abstract: Endometrial polyps (EPs) are localized benign overgrowths at the endometrium, with currently unknown aetiology and pathogenesis. Although symptoms of EP can be alleviated or resolved by hysteroscopic polypectomy, a significant fraction of individuals develop recurrent EPs after initial EP removal. In rare cases, EPs may also undergo malignant transformation. In-depth understanding of the mechanisms that are involved in EP development is urgently needed. Recent works indicate that dysregulations in the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…They reported a correlation between high levels of metalloproteinase and interleukin 1, but not TGF-β, in polyp irrigation samples. In line with Zhu et al [10] and incongruent to Xuebing et al [20], based on our study, polyp lesions showed no TGF-β1 presentation, while 10.9% of normal endometrium expressed this cytokine with no significant statistical difference.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…They reported a correlation between high levels of metalloproteinase and interleukin 1, but not TGF-β, in polyp irrigation samples. In line with Zhu et al [10] and incongruent to Xuebing et al [20], based on our study, polyp lesions showed no TGF-β1 presentation, while 10.9% of normal endometrium expressed this cytokine with no significant statistical difference.…”
Section: Discussionsupporting
confidence: 89%
“…They also demonstrated that stromal cells of the endometrium express this cytokine in a lower amount than glandular cells independent of menstrual cycles. Moreover, Zhu et al [10] presented low concentrations of TGF-β among patients with polyps. Inagaki et al [18] surveyed the level of cytokines in uterine cavity irrigation samples in patients with polyps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that an inflammatory component should be considered, at least in a subset of polyps 11 . Classical inflammatory‐associated factors, including NF‐κB, IFN‐γ and IL‐17, 8–10 are activated in polyps, along with vascular changes secondary to endometritis 19 . The local disturbance in the cellular immune environment observed in EP, such as excess mast cell activity and increased expression of c‐Kit, also suggests that EP are inflammatory lesions 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown that the heterogeneity of the EP subtype may be due to a multifactorial pathogenesis 7 . In addition to estrogen dysregulation, chronic endometrial inflammation was thought to be another contributor to EP development as inflammatory cytokines such as NF‐κB, 8 IFN‐γ and IL‐17 9,10 were activated in polyps. Moreover, endometrial micropolyps were found to have skewed local mononuclear cell composition compared with estrogen‐dependent macropolyps and co‐existed with endometritis 11 .…”
Section: Introductionmentioning
confidence: 99%